Internship satisfaction factors and instruments: a review and research directions for the undergraduate hospitality programs - Ruslan, Syafinaz; Mohamad, Siti Fatimah; Othman, Mohhidin (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2017)
An internship is professional learning experiences that integrates knowledge and theory learned in classrooms with practical application. Most of the local universities embrace internship in their curriculum design as it has been viewed as the platform to enhance students’ skills. However, little study has been done on the internship satisfaction whereby this area should be the focus in assessing an internship. There is a need to study on internship satisfaction in order to maximize the outcomes of the experiential learning that provide benefits to students, universities and organizations. This paper reviewed different factors that contribute to the internship satisfaction, where the factors derived from different contexts of studies. The common factors of the internship satisfaction despite of different contexts are individual factors, university support, job characteristics, organizational environment and also contextual factors. There are several unique factors that are rarely noticed: academic program; program handling; intern’s quality; intern’s expectations on: future employability, career enhancement and the importance of the internship program for the completion of studies; intern’s perceptions- on career related experience, relevant to the field of study, relevant to interests, flexible schedule, communication skills and peer relationship. On the other hand, this paper also reviewed key components from different internship satisfaction instruments, which were conducted in various industries. The common components probed in the instruments are factors influencing internship satisfaction, demographic information and overall satisfaction towards internship experience. While, the distinctive components incorporate general internship satisfaction, assessment of criteria: career skills and career focus, students’ employability options and comments from students on their internship experience. A direction of research for the internship satisfaction instrument comprising its factors, specifically within the context of the undergraduate hospitality program for local universities, is presented in this paper.